LIQUIDITY FORECASTING IN THE SECTOR OF TRADITIONAL AND INNOVATION BASED COMPANIES. IS CCC THE BEST? – THE CASE OF POLAND - Monika Bolek; Bartosz Grosicki (European Scientific Journal, ESJ, 2014)
Liquidity forecasting is connected to strategic plans and valuationmodels. There are some liquidity measures that company may take intoaccount in these processes. Authors wanted to prove that cash conversioncycle is the best measure for liquidity forecasting since it is recommended asa dynamic ratio in the literature. The tests didn‘t confirm the statement butthe conclusions shed the light on other interesting problems with liquidityforecasting. Authors divided the sample for the innovative and traditionalsectors and found the differences between them in the liquidity context.